(untitled) (Journal Of Educational and Psychological Researches, 2015)
This study aims to identify the anxiety pregnant women have of dying, in the light of some Demographic variables in Bethlehem (age, residence, and the mother’s job). The descriptive method was used in this study. To achieve the study purposes, the researchers developed a questionnaire as a tool of study, which consisted of (19) paragraphs ,after been verified of its validity & stability. The researchers distributed questionnaires, and then analyzed them. Results illustrated that the levels of anxiety pregnant women in Bethlehem had of dying was average, with a mean total score of (3.11), and with a standard deviation that had the total score of (0.476). Results also illustrated statistical differences in the pregnant women’s levels of anxiety of dyeing that are attributed to the age variable (31-36), However, there was a statistical value that related pregnant women’s anxiety of dying to the residence variable, in favor of those who lived in the city. Moreover and there were also variations in the levels of anxiety of dyeing during pregnancy relating to the nature of the mother’s job which were in favor of the mother who worked. Thus, and in the light of what the study has reached, the researchers recommends doing further studies and scientific research, that focus on the anxiety of dyeing amongst pregnant women and to apply it to other different social samples. The researcher also recommends the importance of introducing programs that offer psychological and health services for mothers and pregnant women, holding seminars and raising awareness of all the society through the media, concerning the nature of the different psychological status pregnant women go through, and how to handle such situations as well as providing as much emotional balance.